The role of the press in the construction of kurdish collective identity: a case study on "Jin" journal (1918-1919) - Baykuşak, Tahir (İstanbul Bilgi Üniversitesi, 2014)
The aim of this thesis is to trace the process of Kurdish nation-building process through the journal called Jîn, which was published between 1918 and 1922 during the first half of the armistice period. This includes twenty five issues between when the journal began to be published in 07.11.1918 and 02.10.1919. The first half of the armistice period is very similar to Constitutional Era in accordance to Kurdish movement. Similar to Constitutional Era, we come across social and cultural organizations during the armistice period as well. In order to understand this period well, the relationship between Jîn writers and the Kurdish organizations of the time were studied as well as their lives after the establishment of the republic. The publication of Jîn Journal corresponds to an important political breaking point during the armistice period and while it was being explored, comparative reading with its forerunners like Kürdistan Newspaper, Kürt Teavün ve Terakki Newspaper, Rojî Kurd and Hetawî Kurd journals was done. It was thought that a comparative reading would be helpful in order to see the disengagements and continuities in Kurdish nationalist discourse between the Constitutional Era and the armistice period. One of the primary subjects of this thesis is, how some of the main arguments that make out the nationalist discourse like the discussions on origins, ancientness, myths, language, literature and geography were utilized by the Kurdish intellectuals during the process of collective identity construction. In addition, another study was made about the way Jîn Journal approached the population statistics, which provided legitimacy to sovereignty claims during the armistice period.